PENGARUH SUKU BUNGA ACUAN BI, CAPITAL ADEQUANCY RATIO, LOAN TO DEPOSIT RATIO DAN PERTUMBUHAN KREDIT TERHADAP NON PERFORMING LOAN PADA BANK KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - B1021161137, Annisa Dwianty Adinda (Jurnal Manajemen Update, 2021)
Â This study aims to examine and analyze the effect of the Bank Indonesia's Interest rate, Capital Adequancy Ratio (CAR), Loan to Deposit Ratio (LDR) and Credit Growth on Non Perfoaming Loans. This type of research uses quantitative methods, sampling is done by purposive sampling technique and obtained a sample of 38 companies. The discussion was carried out with descriptive statistical analysis, classical assumption test, panel data regression test and hypothesis test and determination test. The test results show that partially the CAR variable has no effect on NPL. The CAR variable has no effect on NPL. The LDR variable has an effect on NPL. Credit Growth variable has no effect on NPL Keywords: Bank Indonesia's Interest rate, Capital Adequancy Ratio (CAR), Loan to Deposit Ratio (LDR), Credit Growth, Non Perfoaming Loans DAFTAR PUSTAKAAbdullah, Thamrin, & Tantri, F. (2014). Bank dan Lembaga Keuangan. Jakarta: PT. Raja Grafindo Persada. Abimanyu, Y. (2004). Memahami Kurs Valuta Asing. Fakultas Ekonomi Universitas Indonesia. Adâ€™hadini, N. D., & Kusumawardhani, A. (2016). Analisis Pengaruh Bank Size, Ldr, Bopo, Pertumbuhan Kredit dan Car Terhadap Non Perfoarming Loan (Studi Kasus Pada Bank Umum Konvensional Yang Terdaftar Di BEI Tahun 2010-2014) . Journal of Management, 5(3). Agus, W. (2007). Ekomometrika Teori dan Aplikasi. Yogyakarta: Ekonisia FE UIL. Anjom, W., & Karim, A. M. (2016). Relationship Between Non-Performing Loans And Macroeconomic Factors With Bank Specific Factors: A Case Study On Loan Portfolios â€“ Saarc Countries. Journal of Finance and Risk Management, 7(2). Baltagi, B. H. (2005). Econometric Analysis of Data Panel. England: John Wiley & Sons Ltd. Baltagi, B. H. (2008). Econometrics. New York: Springer-Verlag Berlin Heidelberg. Bambang, W., & Aristanti, W. (2007). Ekonomi & Akuntansi Mengasah Kemampuan Ekonomi. Jakarta: PT. Grafindo Media Pratama. Barus, A. C., & Erick. (2016). Analisis Faktor-Faktor yang Mempengaruhi Non Performing Loan Pada Bank Umum di Indonesia. Jurnal Wira Ekonomi Mikroskil, 6(2), 113-122. Boediono. (2014). Ekonomi Internasional. BPFE UGM. Darmawi, H. (2011). Manajemen Perbankan. Jakarta: Bumi Aksara. Dendawijaya, L. (2000). Manajemen Perbankan. Jakarta: PT. Gramedia Pustaka Utama. Diyanti, A., & Widyarti, T. E. (2012). Analisis Pengaruh Faktor Internal dan Eksternal Terhadap Terjadinya Non-Performing Loan (Studi Kasus Pada Bank Umum Konvensional yang Menyediakan Layanan Kredit Pemilikan Rumah Periode 2008-2011). Journal of Management, 1(2), 290-299. Fahmi, I. (2012). Analisis Kinerja Keuangan. Bandung: Alfabeta. Ghozali, I. (2016). Aplikasi Analisis Multivariete dengan Program IBM SPSS 23 Edis 8. Semarang: Universitas Indonesia. Ismail. (2013). Manajemen Perbankan. Jakarta: Kencana Prenamedia Group. Kamus Besar Bahasa Indonesia.Kasmir. (2008). Bank dan Lembaga Keuangan. Jakarta: PT. Raja Grafindo Persada. Keeton, W. R. Does Faster Loan Growth Lead To Higher Loan Losses? 84(2). Kuncoro, M., & Suhardjono. (2011). Manajemen Perbankan : Teori dan Aplikasi . Yogyakarta: BPFE. Kusuma , E. C., & Haryanto , A. M. (2016). Analisis Pengaruh Variabel Kinerja Bank (CAR, ROA, BOPO dan LDR), Serta Pertumbuhan Kredit dan Kualitas Kredit Terhadap Non Performing Loan (Npl). Journal of Management, 5(4), 1-13. Linda, M. R., & Megawati. Pengaruh Inflasi, Kurs dan Tingkat Suku Bunga Terhadap Non Performing Loan Pada PT. Bank Tabungan Negara (PERSERO) Tbk Cabang Padang. Journal of Economic and Economic Education, 3(2), 137-144. Mahmudah, R. (2013). Analisis Faktor-faktor yang Mempengaruhi Non Perfoarming Loann di Sulawesi Selatan (Skripsi yang di publikasi) Universitas Hasasanudin, Indonesia.Nachrowi, N. D., & Usman, H. (2006). Pendekatan Populer dan Praktis Ekonometrika Untuk Analisis Ekonomi dan Keuangan. Jakarta: LPFE Universitas Indonesia. Peraturan Bank Indonesia No.15/15/PBI/2013 Tentang PerbankanPutri, E. P. (2016). Pengaruh Faktor Internal dan Eksternal Terhadap Kredit Bermasalah Bank Umum Konvensional dan Pembiayaan Bermasalah Bank Umum Syariah. 4(2). Rahamanda, R., & Musdholifah. (2016). Pengaruh Loan To Deposit Ratio, Capital Adequacy Ratio, dan Gross Domestic Product Terhadap Non Performing Loan Pada Bank Pembangunan Daerah di Indonesia Periode 2013-2014. Jurnal Ilmu Manajemen, 4(3), 1-9. Saputro, A. R., Sarumpaet, S., & Prasetyo, T. J. (2019). Analisa Pengaruh Pertumbuhan Kredit, Jenis Kredit, Tingkat Bunga Pinjaman Bank dan Inflasi Terhadap Kredit Bermasalah. Jurnal Ekonomi, Keuangan, Perbankan dan Akuntansi, 11(1). Simon, A. B. (2010). Analisis Dampak Terjadinya Shock Variabel Moneter Terhadap, 87-100.Siregar, S. (2010). Statistika Deskriptif Untuk Penelitian. Jakarta: PT. Rajagrafindo Persada. Siswanto, S. (2008). Good Corporate Governance. Jakarta: PT. Damar Mulia Pustaka. Sugiyono. (2009). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta. Sugiyono. (2012). Metode Penelitian Kombinasi. Bandung: Alfabeta. Sugiyono. (2013). Metode Penelitian Pendidikan Pendekatan Kuantitaif, Kualitatif dan R&G. Bandung: Alfabeta. Sugiyono. (2015). Metode Penelitian Pendidikan (Pendekatan Kuantitatif, Kualitatif, R&FG). Bandung: Alfabeta. Surat Edaran Bank Indonesia No. 06/03/DPNP/2004.Surat Edaran Bank Indonesia No.6/23/DPNP/2009.Surat Edaran Bank Indonesia No. 13/1/PBI/2011Syahid, D. C. Pengaruh Faktor Eksternaldan Internal Terhadap Kredit Bermasalah Serta Dampaknya Terhadap Cadangan Kerugian Penurunan Nilai Menurut Psak 55.Taswan. (2006). Manajemen Perbankan. Yogyakarta: UPP STIM YPKP. Triandaru, S., & Budisantoso, T. (2006). Bank dan Lembaga Keuangan Lain. Jakarta: Salemba Empat. Undang-Undang Perbankan Nomor 7 Tahun 1992.Undang-Undang Republik Indonesia Nomor 10 Tahun 1998 Tentang Perbankan.Yusuf, M. R., & Fakhruddin, F. (2016). Analisis Variabel Makro dan Rasio Keuangan Terhadap Kredit Bermasalah. Jurnal Ekonomi dan Kebijakan Publik Indonesia, 3(2), 93-108.